Ewolucja kryteriów subwencjonowania gmin w Polsce w latach 1991-2004 - Miszczuk, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the process of shaping of local finances four periods of subsidizing of self-government in gminas can be distinguished. These periods have been set by four different acts regulating the issue of supplying gminas with funds from the budget. In the first period, functioning in the years 1991-1993, the main criterion of assigning subsidies/ subventions was the number of people. Other criteria with less importance were linked with various functions that the self-government played, with an economic development or with the need to protect environment and also with the fiscal potential of a given gmina. The following two periods from 1994-1998 and 1999-2003 were also characterised by similar ideas in the range of subventions/ subsidies. One of a major criterion was, similarly to the first period, the number of people, but simultaneously the number of pupils attending schools run by a gmina became also important for the amount of money received from the budget, and the fiscal potential. However, other criteria included in the previous period, which conditioned the amount of subsidy being granted, were given up. The fourth period which has been functioning since 2004 does not basically differ from the previous ones, but certain criteria previously used, have been accepted in new forms/shapes, e.g. the fiscal potential and the number of pupils. Simultaneously, a new criterion has been introduced - the population density- taking into account, at the same time, the total land area as an important factor in shaping of subsidies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 469-479